Au‐Free Ohmic Contacts and Their Impact on Sub‐Contact Charge Carrier Concentration in AlGaN/GaN Heterostructures. Issue 2 (16th November 2021) - Garbe, Valentin; Schmid, Alexander; Seidel, Sarah; Abendroth, Barbara; Stöcker, Hartmut; Doering, Philipp; Meyer, Dirk C.; Heitmann, Johannes
Abstract : The impact of an Au‐free Ti/Al/Ti/TiN (20/100/20/80 nm) ohmic contact metallization on an Al0.21 Ga0.79 N/GaN heterostructure is investigated. Using the transfer length method and Hall measurements, the sheet resistance and the carrier concentration below the contact are analyzed, depending on the post‐deposition annealing temperature. It is shown that with increasing annealing temperature, the carrier density below the contact is enhanced. This is caused by the contact formation mechanism, leading to an extremely low contact end resistance to the sub‐contact region of 0.04 Ω mm. However, while the sub‐contact semiconductor resistance is low, the contact (front) resistance to the device channel is 0.74 Ω mm after annealing at 900 °C, indicating a depletion of the sub‐contact 2D electron gas because of alloy formation. Abstract : The impact of an Au‐free Ti/Al/Ti/TiN ohmic contact metallization on an AlGaN/GaN heterostructure is investigated with regard to carrier concentration and sheet resistance below the contact. It is shown that with increasing annealing temperature, the carrier density below the contact is highly enhanced, leading to an extremely low contact end resistance of 0.04 Ω mm.